FROM BÂKÎ TO NEDÎM: CONTENTION FOR LOVE AND WRITHE FOR LOVE - Aysun ÇELİK (International Journal of Eurasia Social Sciences, 2017)
Love in our classic poetry is based on suffers of the beloved; anguish and agonies of the lover. Anyhow the fact that dignity of the beloved is determined according to the inflictions; resource and greatness of the lover are evaluated by fortitude for destructions. Transcendency of the love is in direct proportion to the period that the lover remained separate from its beloved. Although this situation brings lovers structured as melancholic and lovers developed with hankering romanticism into being, almost every poet puts such love in for. In this study, attitudes of Bâki and Nedîm for love are researched in consequence of similar prosperity environments of the periods they lived and fondness of spirits for each other. The term of “contention for Love” allude to the points of view of Bâki and Nedîm for love. As to “writhe for love” allude to the fact that lovers become bent double by the burden of love and changing their ways in the wake of love.